Decolorization enhancement by optimizing azo dye loading rate in an anaerobic reactor. Issue 55 (20th May 2016) - Cui, Min-Hua; Cui, Dan; Liang, Bin; Sangeetha, Thangavel; Wang, Ai-Jie; Cheng, Hao-Yi
Abstract : An up-flow anaerobic sludge blanket (UASB) reactor was developed to investigate the effect of azo dye loading rate on the decolorization performance and microbial community. Abstract : An up-flow anaerobic sludge blanket (UASB) reactor was developed to investigate the effect of azo dye loading rate on the decolorization performance and microbial community. The results indicated that the decolorization efficiency decreased from 95.84 ± 2.60 to 62.98 ± 8.66% with the azo dye loading rate increasing from 100 to 800 g m −3 d −1 . The inhibition of the high azo dye loading rate on the microbial activity was reversible. The decolorization efficiency rose with the azo dye loading rate decreasing and recovered to 92.15 ± 3.86% at an azo dye loading rate of 600 g m −3 d −1 . The results of 16S rRNA gene sequencing based on the high-throughput Illumina MiSeq sequencing showed that the microbial diversity of the sludge in UASB was reduced compared to the inoculum. Proteobacteria (40.51%) and Firmicutes (33.17%) were enriched. Enterobacter and Enterococcus with relative abundances of 26.99% and 20.38% were the most enriched genera, which were also functional for azo dye reduction.